Perceptions of farm size heterogeneity and demand for group index insurance - Kathryn N. Vasilaky; Sofía Martínez Sáenz; Radost Stanimirova; Daniel Edward Osgood (Games, 2020)
Weather insurance is a financial instrument proposed to increase coverage of unprotected weather shocks in developing countries. Structuring sales as group-based products has been argued as a strategy to increase the attractiveness of index insurance, raising the question as to what impacts farmer demand for group insurance choices. We test if farmers prefer to purchase real-world insurance products as groups, and if groups of more similar individuals are more likely to demand group over individual index insurance for the upcoming season. We exogenously assign farmers into groups of similar versus dissimilar perceived farm size. We find that farmers, when offered, prefer group over individual insurance contracts, and that groups of farmers who perceive each other to be more similar in farm size are more likely to purchase in a group, but purchase less insurance on average.
Keywords: D91; O12; D71; Q140; 330; agriculture; group contracts; index insurance; risk